ECOLOGICAL AND ECONOMIC COMBINATION AND COORDINATION OF ACTIONS OF THE BASIS FOR THE DEVELOPMENT OF UKRAINE - Zhuravska, Nataliia; Grakhov, Andriy (SWorld-Ger Conference proceedings, 2024)
Approaches to assessing the impact of ecology on the economy are presented, specific examples of the involvement of green technologies for the strategic development of business activities for resource conservation, waste reduction for the regulation of en